SEMANTIC FIELDS AND EFL/ESL TEACHING - Gültekin Boran (Informascope, 2018)
The vocabulary of a language is a system of interrelated lexical networks but not a collection of independent items. Vocabulary of a language is organised into fields within which words interrelate and define each other in various ways. Sense relations are not enough to explain the relation between some lexical items. For example, we cannot explain the relation between patient and hospital through synonymy, antonym, hyponymy, polysemy or homonymy, but we can say that they belong to the same semantic field which we can label as 'health'. In this paper, semantic field also known as word field, lexical field, field of meaning, and semantic system is explained by giving supporting examples. Besides, some implications for Teaching English as a Foreign Language/Teaching English as a Second Language (TEFL/TESL) are suggested